Convenient Conversion of Palm Fatty Acid Distillate to Biodiesel via Rice Husk Ash Catalyst - Zainab, Ngaini; Nurfarahen, Jamil; Rafeah, Wahi; Farra Diana, Shahrom; Zainal Abiddin, Ahmad; Saba, Farooq (Springer, 2021)
Silica-based heterogeneous catalyst derived from rice husk ash (RHA) was used for the transformation of palm fatty acid distillate (PFAD) into biodiesel. The production of the biodiesel from PFAD was conducted via esterification and transesterification employing Huskcatacid and Huskcatbase, respectively. The biodiesel was analyzed from different parameters, i.e., amount of catalyst, oil to methanol ratio, temperature, and reaction times. The outcomes depicted Huskcatacid was efficient for PFAD esterification to produce 91.6% ester with 5 wt% catalysts and 5:1 (MeOH:PFAD), followed by the transesterification using 1 wt% Huskcatbase in 3:1 (MeOH:oil) to generate 99.73% biodiesel with a high percentage of methyl oleate (57.86%) and methyl palmitate (34.43%). Huskcatacid and Huskcatbase depicted a high surface area (7.362 m2/g and 14.493 m2/g) and high porosity (2.726 × 10−3 cm3/g and 4.985 × 10−3 cm3/g), respectively, that contributed to the efficient esterification and the easy separation of glycerol. The PFAD-derived biodiesel was tested on the Megatech®-Mark III engine and confirmed the proportional torque (ɽ) increment with the loading of B100 biodiesel. Rice husk showed promising outcomes as solid-support heterogeneous catalysts and the production of value-added products to reduce the agricultural waste management issues.